The essential characteristics of industrialised building system - Thanoon, Waleed Abdulmalik; Lee, Wah Peng; Abdul Kadir, Mohd Razali; Jaafar, Mohd Saleh; Salit, Mohd Sapuan (2003)
In essence, the growing demand for affordable housing, increasing construction costs, lower productivity rate, and heightened concern for energy-efficiency has prompted the Malaysia’s construction players to realise the immense benefits of industrialised building system. Despite its advantages, the adoption of industrialised building system has been low in gaining popularity, partly due to lack of awareness and coordination among the relevant parties. Indeed, the need to be competitive in the emerging global market has prompted the local construction players to be more open minded and receptive to novel building technology. In other word, the awareness of current trends and latest innovation in industrialised building system is essential in order to survive in the competitive market. Therefore, this article seeks to enlighten the construction industry players about the characteristics of an industrialised building system as well as its major advantages and disadvantages.